Penggunaan Larutan Soil Stabiliser Dan Semen Terhadap Nilai CBR Tanah Lempung Jalan Poros Maros Camba - Sultan, Arsy Fakroh Ibnu; Yusuf, Andi Rumpang; Cangara, Satriawati (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Currently, soil stabilization is being developed using environmentally friendly chemicals. This material is called Soil Stabilizer Solution. This research aims to analyze the characteristic and mechanical properties of soil and analyze the effect of adding soil stabilizer solution and cement on CBR values. Soil plays an important role as a supporting foundation. So from the mixing method applied to mechanical measurements on real soil, the compaction measurement uses 5 soil samples of 100% of 2kg weight without cement and SS solution, as well as the addition of 1.5% SS solution with a fixed composition using 100% soil without cement, and with the addition of 1.5% SS solution plus 4%, 6%, 8% PCC cement which reduces the soil so that the soil used is 96%, 94% and 92% of the total weight of the soil. For CBR, 3 original soil samples are used and the composition of each variation the same, with a sample weight of 5kg, the CBR value of the Original Soil is 10.22% while the increase in adding 1.5% SS Solution + 0% Cement is 18.70%, as well as the increase in adding 1.5% SS Solution + 4 %,6%,8%, experiencing an increase respectively, namely 26.85%, 31.71% and 44.79%, the use of SS solution and PCC cement for soil stabilization can increase the CBR value in the bearing capacity of clay soil.